2004
DOI: 10.1016/j.bbamem.2004.06.022
|View full text |Cite
|
Sign up to set email alerts
|

OVCAR-3 cells internalize TAT-peptide modified liposomes by endocytosis

Abstract: For cytosolic delivery of liposomes containing macromolecular drugs, such as proteins or nucleic acids, it would be beneficial to bypass endocytosis to prevent degradation in the lysosomes. Recent reports pointed to the possibility that coupling of TAT-peptides to the outer surface of liposome particles would enable translocation over the cellular plasma membrane. Here, we demonstrate that cellular uptake of TAT-liposomes occurs via endocytosis rather than plasma membrane translocation. The coupling of HIV-1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…Similar results have been obtained for PEI [36,37]. Thirdly, data collected by Fretz et al [38] strongly suggest that TAT coupled to liposomes does not lead to an advantageous route of internalization compared to the unmodified liposomes. Similar to PEI, recent studies suggest uptake of CPPs is via clathrin-and caveolaemediated endocytosis, and macropinocytosis [1].…”
Section: Transfection Efficiency In Vitro and In Vivosupporting
confidence: 80%
“…Similar results have been obtained for PEI [36,37]. Thirdly, data collected by Fretz et al [38] strongly suggest that TAT coupled to liposomes does not lead to an advantageous route of internalization compared to the unmodified liposomes. Similar to PEI, recent studies suggest uptake of CPPs is via clathrin-and caveolaemediated endocytosis, and macropinocytosis [1].…”
Section: Transfection Efficiency In Vitro and In Vivosupporting
confidence: 80%
“…PEGliposomes (PEG-L) without an antibody attached were used as a control. Due to the PEG-layer surrounding these liposomes, the cellular association and uptake by OVCAR-3 cells is low as shown previously (9,19).…”
Section: Liposome Characteristicsmentioning
confidence: 86%
“…FACS analysis following trypsin treatment indicated a relatively slow rate of uptake, comparable to that of classical markers of endocytosis. Since then, many other studies have also observed inhibition of cellular uptake at 4°C and with chemical means that induce energy depletion, indicating an energy-dependent process as the major route for the internalization of cell-penetrating peptides [27][28][29][30][31][32][33].…”
Section: Direct Translocation Endocytosis: An Either/or Discourse?mentioning
confidence: 99%